Estudio de la pasivacion de la aleacion Co-Cr-Mo en suero fisiologico - Ramires, I.; Rocha, L.; Codaro, E. N.; Guastaldi, A. C. (My University, 1999)
Results are presented on the mechanism of passivation of Co-Cr-Mo biological implant alloys in physiological serum using open circuit potentiometry, potentiodynamic curves, and electrochemical impedance spectroscopy. The potential dependence of impedance data and the analysis of the parameters obtained indicate a progressive diminution of the initial layer thickness and the simultaneous formation of a second higher resistive layer. In more severe conditions than the existent in human body, the metallographic examination of the alloy surface shows localized corrosion in interdendritric regions. Elemental analysis of the surface reveals the presence of higher chromium content in these regions. The presence of chlorine was not detected, which suggested that during preferential attack, soluble species are also formed.
Study of passivation of Co-Cr-Mo alloy in physiologic serum
Keywords: Electrochemistry; Implants (surgical); Passivation; Spectroscopic analysis; Open circuit potentiometry; Potentiodynamic curves; Cobalt alloys